Introduction: New Approaches to the League of Nations - Ikonomou, Haakon A. (Culture and History: Student Research Papers, 2023)
This brief introduction aims to situate this special issue’s contributions within the broader historiographical shifts in the scholarship on the League of Nations. Particularly, it highlights how global, digital, institutional and biographical approaches have helped reveal the sheer scale and complexity of the League’s role in interwar world ordering. The second aim of the introduction is to shed light on the work process leading up to this special issue: it involved several research-based courses, an integrated digital history project, and tailored seminars to turn exams into articles.